2017
DOI: 10.3945/ajcn.116.140798
|View full text |Cite
|
Sign up to set email alerts
|

Nonfermented milk and other dairy products: associations with all-cause mortality,

Abstract: Background: A positive association between nonfermented milk intake and increased all-cause mortality was recently reported, but overall, the association between dairy intake and mortality is inconclusive. Objective: We studied associations between intake of dairy products and all-cause mortality with an emphasis on nonfermented milk and fat content. Design: A total of 103,256 adult participants (women: 51.0%) from Northern Sweden were included (7121 deaths; mean follow-up: 13.7 y). Associations between all-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 40 publications
4
61
0
Order By: Relevance
“…fermented and non-fermented milk) with all-cause mortality and found that cheese intake was negatively associated with mortality, in line with previous results from other two large Swedish studies [11, 12]. In the present study, the association between cheese and mortality did not show any dose–response and maintained statistical significance despite somewhat decreased strength along the follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…fermented and non-fermented milk) with all-cause mortality and found that cheese intake was negatively associated with mortality, in line with previous results from other two large Swedish studies [11, 12]. In the present study, the association between cheese and mortality did not show any dose–response and maintained statistical significance despite somewhat decreased strength along the follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…For every glass of milk, which in Sweden is primarily pasteurized milk, the adjusted hazard ratio of all-cause mortality was 1.15 (1.13-1.17) in women and 1.03 (1.01-1.04) in men, respectively. A recent study from Northern Sweden including 103,256 adult participants reported that high consumers of nonfermented milk (≥ 2.5 times/day) had a 32% increased hazard (HR: 1.32; 95% CI 1.18, 1.48) for allcause mortality compared with that of subjects who consumed milk ≤ 1 time/week [191]. In contrast, fermented milk intake and cheese intake were negatively associated with mortality [191].…”
Section: Atherosclerosis Cardiovascular and Overall Mortalitymentioning
confidence: 99%
“…A recent study from Northern Sweden including 103,256 adult participants reported that high consumers of nonfermented milk (≥ 2.5 times/day) had a 32% increased hazard (HR: 1.32; 95% CI 1.18, 1.48) for allcause mortality compared with that of subjects who consumed milk ≤ 1 time/week [191]. In contrast, fermented milk intake and cheese intake were negatively associated with mortality [191]. A systematic review and updated dose-response meta-analysis of prospective cohort studies partially funded by dairy associations reported a 7% lower risk of stroke with an increment of 200 g milk daily [192].…”
Section: Atherosclerosis Cardiovascular and Overall Mortalitymentioning
confidence: 99%
“…Both long-term interventional studies and epidemiological data indicate that dairy products are a heterogeneous food group with various effects on blood lipids (28) and all-cause mortality (29,30) . For the first time, we recently demonstrated divergent postprandial TAG and HDL-C responses (measured as the 0-6 h incremental AUC (iAUC 0-6h )) between different dairy products in healthy adults (31) , with a borderline significant effect of sex on serum TAG-iAUC 0-6h .…”
mentioning
confidence: 99%